Қарақалпақ халық той жырларында импровизация қубылысы (SCIENCE and SOCIETY, 2023)
The article says that wedding songs in the ancient and modern process of the Karakalpaks are performed with an im- provisational program. A type of program songs in Karakalpak folklore, the program bet ashar (kelin salom) is an example of ethno- folklore oral creativity inherited from our ancestors. Examples explain the creation of the «bet ashar» program using the improvisation method.